Politiquisticos ovaries and infertility - Benavente Lozada, Benjamin (2015)
Ovarian pathology has always aroused interest gynecologists, either because it gives rise to disease entities or because its spread is the expression of hormonal, functional disorders or oránicos, systems and bodies linked to the ovary.